Comprehensive approach to the efficiency assessment of the business model of the aviation enterprise based on business process innovation - Zarina Poberezhna (PC Technology Center, 2021)
The improvement of theoretical and methodological approaches to the formation of innovativeness of business processes of enterprises has been carried out. A model of innovativeness of business processes has been formed, which takes into account the principles, goals, methods of improving the management of business processes and the factors of influence on them.